Place-names of the Whittlewood area - Forward, Eleanor J. (2008)
The recent work of D. H. Green and others on the benefits of combining linguistic, archaeological and historical evidence has highlighted the importance of cross-disciplinary collaboration to early medieval studies. In this context, the Whittlewood Project (WP) lays important foundations for future projects, both in the UK and elsewhere, which seek to understand local settings in greater depth than any single discipline could permit.